Determination of Period of RC Buildings by the Ambient Vibration Method - Mehmet Inel; Hayri Baytan Ozmen; Bayram Tanik Cayci (Advances in Civil Engineering)
Determining the dynamic properties of structures is important for understanding their seismic behaviour. Ambient vibration signal measurement is one of the approaches used to determine the period of structures. Advantages of this method include the possibility of taking real-time records and presenting nondestructive and rapid solutions. In this study, natural vibration periods are calculated by taking ambient vibration signal records from 40 buildings. The height of the building, infill wall effect, presence of seismic retrofit, and presence of damage are taken into consideration, and their effects on natural vibration periods are investigated. Moreover, the results are compared with the analytical methods to reveal the differences. A significant correlation between the period and height of the building is observed. It is seen that the natural vibration periods of the buildings decrease by 7% to 30% (15% on average) due to infill wall contribution. However, the efficiency of infill walls decreases as the building height increases. Another significant result is that adding shear walls substantially decreases the vibration period values by 23% to 33% with respect to the shear wall ratio. When the analytical estimates and measured building period results are compared, it is seen that analytical models have closer period estimates before infill walls are implemented. The limited data in scope of the study suggest that significant differences may present in the analytical and measured periods of the buildings due to infill wall contributions.